Does Corporate Social Responsibility Affect Liquidity Risk? Evidence from GCC and non-GCC countries - Khemiri, Mohamed Ali (International Journal of Economics and Financial Issues, 2025)
This study investigates the CSR-liquidity risk nexus in the banking sector of the MENA region. Growing concerns about financial stability and sustainable banking establishments prompt this study to examine whether CSR activities may reduce liquidity risk in an economic environment of volatility and regulatory disparity. A panel dataset of 40 commercial banks operating in ten MENA countries from 2010 to 2022 was used in the analysis, with estimation carried out with the System Generalized Method of Moment estimator to take care of issues of endogeneity and dynamics. To better reflect regional specificities, the sample gets further disaggregated into the GCC region and non-GCC region. The results of the estimations show that CSR is negatively related to liquidity risk in the whole sample. This reveals that socially responsible banks suffer from lesser liquidity constraints. However, the insignificance of this relationship for banks outside the GCC countries could be due to the relatively weaker institutional structures and low awareness of CSR among stakeholders, whereas for banks inside the GCC, CSR does significantly affect liquidity risk management because of better institutional provisions and expectation standards. These results are helpful for bank mangers and policymakers by pointing out the importance of including CSR as part of risk management. The study contributes to literature with new knowledge about the relationship between CSR and liquidity risk in emerging economies, particularly in the context of the MENA banking systems.